DORMAN (DORONGAN ANAK MUDA YANG MANDIRI) DALAM MENINGKATKAN FOKUS BERWIRAUSAHA - Siagian, Supriadi; Sjukun, Sjukun; Peranginangin, Jimmy (Jurnal ABDIMAS Budi Darma, 2024)
The aim of this socialization is to provide encouragement to students at LKP Nurma to focus and be enthusiastic about entrepreneurship. To solve the problems that exist in LKP, the socialization of entrepreneurial encouragement provides understanding and the importance of becoming a young entrepreneur. This socialization is designed for all students at LKP Nurma who are currently undergoing sewing course training. This training method includes outreach, training, application of technology, mentoring and program sustainability. This socialization succeeded in increasing enthusiasmand understanding regarding MSME funding programs, time management, service quality and marketing via digital platforms. It is hoped that, for sustainability, students will maintain their entrepreneurial spirit and be able to activelyutilize all digital platforms and other supporting applications.